LEGAL PROTECTION POLICY FOR CHILDREN AS RAPE VICTIM IN GETTING REHABILITATION SERVICES - Antory Royan Adyan (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThis study focused on identifying the rules or norms of positive law, relating toArticle 64 paragraph (3) letter a of Law No.23 of 2002 carried throughÂ rehabilitation efforts, both within the institution and outside the institution. Background inequity of treatment between the rights of offenders and the rights of victims in the criminal justice system. positive in criminal law today is more emphasis on the protection of nonphysical rehabilitation of mental disorder be done